FACING SOLO RAYA METROPOLITAN CITY: ANALYSIS OF THE DEVELOPMENT PLANNING - Rita Noviani; Lutfi Muta'ali; Nasruddin Nasruddin (GeoEco, 2018)
Since 2010 Solo Raya has became part of the metropolis candidates that will continue to grow along with the agglomeration of Jogjakarta and Semarang. The problems that trail is the tendency of metropolitan magnitude that resulted in less functioning of the city as a catalyst for regional development. Further impact is the lagging of small and medium-sized cities (Tjahjati, 1995). The development of urban system is determined by both the comparative advantage and the competitive advantages, such as location, natural resources and human resources (Metropolitan Directorate, 2003), so that in planning the development it should focus on the ability to cooperate or synergize between regions (spatial synergism) either in urban and rural area or on a wider scale, cooperation between cities.The purpose of this research was to arrange aspects and decision criteria in developing metropolitan area of Solo Raya. The method used is literature study approach which is then analyzed descriptively.The result of analysis showed that in metropolitan area of the world there are 4 (four) main characteristics and problems, they are: (1) city as center of population, economy and government activity, (2) city with environmental problems (air, land and water), as a result of population density, public transportation, and garbage, (3) city with problems in the land aspect (land prices and housing provision) and (4) city with problems on social aspects (criminals and terrorists). The formulation of metropolitan area development planning is done with 3 (three) considerations, they are: (1) avoiding high social segregation between and among regions, (2) creating a balance population mobility and intra and inter-regional services (spirit of togetherness), (3) creating a regional economy (growth, equity and welfare) based on the local potential which has inter-regional connectivity (harmonization). Aspects and criteria are: regional management (spatial planning policy, regional competitiveness, regional marketing, inter-regional cooperation), urbanization (migration, urbanization, agglomeration and conurbation, social integration), economic development (economic growth, employment, economic equalization, urban poverty), regional connectivity (transportation, rural-urban linkage, territorial function), and environment (environmental supporting capacity, disaster risk, environmental degradation, disaster mitigation). The decision priorities include: Industrial City, Service City, City of Tourism and Culture, Trade City, and Agriculture.